현대 기업에서 요구되는 디자인 리더쉽의 책무와 필요역량 연구 - 원호연; Won Ho Yeon (기초조형학연구, 2023)
본 연구는 기업에서 디자인 조직을 이끄는 디자인 리더쉽의 책무와 역할을 재고하고 기능적 변화를 파악하는데 목적을 둔다. 현대 기업에서 디자인이 제품이나 서비스의 핵심 경쟁력이 되면서, 인하우스 디자인 기능과 조직의 규모의 확장과 위상도 높아지며, 더불어 디자인 조직을 이끄는 디자인 최고책임자, 경영자, 지도자의 역할을 하는 디자인 리더쉽의 책무와 역할도 커지고 있다. 그동안 디자인 경영도입으로 조직의 체계화가 이루어졌지만, 최근 4차산업혁명 시대에는 산업환경이 빠르게 변화함에 따라 리더쉽의 패러다임도 변화가 이루어지고 있다. 이 같은 환경속에서 현대 기업이 요구하는 디자인 리더쉽의 임무, 역할과 책임 및 필요한 역량이 무엇이며, 또한 어떻게 변화되는가를 연구하고자 한다. 연구 방법으로는 디자인 리더쉽의 개념과 책무에 대한 이론적 고찰을 하고. 선행연구를 통해 내용 분석을 위한 프레임워크를 구성한다, 각각의 세부 필요역량을 파악을 위해 글로벌 채용사이트에 공지된 정보를 수집하고, 이를 토대로 기업에서 필요로 하는 디자인 리더쉽의 임무, 역할과 책임 및 필요자격을 분석한다. 도출된 결과를 보면, 현대 기업에서는 디자인 리더쉽의 여러 책무 중에 기업 가치를 재고하며 디자인 조직을 운영하는 관리자의 역량도 기본적으로 중요하지만, 그보다 디자인 프로젝트를 성공적으로 관리와 감독하는 디자인 전문가 역량이 더욱 요구된다는 점이다. 역할과 책임(R&R) 부분에서도 디자인 전문역량으로 전략 수립과 혁신 도모가 좀 더 높게 나타났고, 필요자격도 마찬가지로 디자인 전문성이 가장 요구되었다. 이는 기업마다 디자인 경영시대를 넘어 기업의 생존과 시장 경쟁력을 도구로 디자인 혁신성과 전문성이 요구됨에 따라, 디자인 리더쉽의 필요역량도 변하고 있다고 볼 수 있다. The purpose of this study is to reconsider the role and responsibility of design leadership leading design organizations in companies and to identify the functional changes. As design has become the core competitiveness of products or services in present companies, the size and status of in-house design functions and organizations are increasing, in addition the responsibility and role of design leadership which serves as the chief design officer, manager, and leader who leads the organization, is growing. In the meantime. the organization has been systematized by design management, but in this era of the 4th Industrial Revolution, the paradigm of leadership is also changing as the industrial environment rapidly changes. In this environment, this study aims to study what the tasks, roles, responsibilities and competencies of design leadership required by present companies are, and how they are changing. As a research method, theoretical considerations are made on the concept and responsibility of design leadership. A framework for content analysis is constructed through prior research. In order to identify each specific required competency, information announced on global recruitment sites is collected, and based on this, the mission, role, responsibility, and required qualifications of design leadership required by the company are analyzed. According to the results, among the various responsibilities of design leadership in present companies, basically the manager’s ability to reconsider corporate values and run a design organization is fundamental but the design expert’s ability to successfully manage and supervise design projects is much more required. In the role and responsibility(R&R) perspective, strategy building and innovation leading were shown to be higher as design expertise also design professional ability was the most demanded for qualifications. As each company requires design innovation and expertise as a tool for survival and market competitiveness beyond the design management era, the required competency for design leadership is also changing.